Soybean oil based resin: A new tool for improved immobilization of alpha-amylase - OGAN, AYŞE; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (WILEY, 2006)
Acrylated epoxidized soybean resin has been utilized to immobilize the alpha-amylase via UV-curing technique. Among the numerous methods that exist for enzyme immobilization, entrapment and covalent binding are the focus of this study. The properties of immobilized enzyme were investigated and compared with those of the free enzyme. Upon immobilization by the two methods, the catalytic properties of the enzyme were not considerably changed as compared with that of nonimmobilized form; enzyme. The free enzyme lost its activity completely in 20 days, where as storage and repeated usage capability experiments demonstrated higher stability for the immobilized form. Immobilized enzyme prepared by attachment method possesses relatively higher activity compared with the activity of those obtained by entrapment method. (c) 2006 Wiley Periodicals, Inc.
Keywords: epoxy acrylates; UV-curing coating; alpha-amylase; immobilization; enzyme activity; SUPPORTS; STABILITY; ENZYMES